The role of job satisfaction as a mediator in the relationship between integrity and organizational citizenship behavior amongst the Malaysian police officers - Ibrahim, Muhamad Ariff; Abdul Aziz, Siti Fardaniah; Wan Sulaiman, Wan Shahrazad; Ibrahim, Amalina; Mokhtar, Mostafa Kamal (Hampstead Psychological Associates, 2020)
The present study was conducted to observe the effects of job satisfaction as mediator on the relationship betweenintegrity perception and organizational citizenship behavior amongst PDRM enforcement officers. Subjects were 282 ennforcement officers who were selected using stratified random sampling method ranging from Constables and Sub-inspectors from 6 Distcrict Police Offices in the state of Selangor.The present study utilized three questionnaires includingIntegrity Questionannire, Citizenship OrganisationalBehaviour Questionnaire,Minnesota Satisfaction Questionnaire (MSQ).Structural Equation Modelling showed that integrity perception affect job satisfaction with β=0.77, p<0.05; and job satisfaction affect Citizenship Organisational Behaviourwith β=0.70, p<0.05. Meanwhile, perception integrity can affect the Citizenship Organisational Behaviour directly with β=0.23, p<0.05. To conclude, job satisfaction plays role as partial mediator in on the relationship between integriy perception and organizational behavior amongst the enforcement officers.Results also showed that enforcement officers who posse’shigh perception of integrity feel satisfied with their jobs and in the long run contribute to a good practice of citizenship organisational behavior which indirectly results in a positive impact to the organization. This article suggests future studies and the practical solution in empowering the practice of good organizational behavior amongst enforcement officers